2010
DOI: 10.1001/archsurg.2010.10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Unknown Primary Tumors in Patients With Neuroendocrine Liver Metastases

Abstract: For patients with NET liver metastases and unknown primary tumor, surgical exploration effectively identifies and resects occult primary tumors that are often located in the small intestine. Primary tumors are usually small and multifocal, so careful palpation of the small intestine is essential. Before patients are considered for surgery, a multidisciplinary team assessment and evaluation consisting of computed tomography, somatostatin receptor scintigraphy, and upper and lower endoscopy should be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 16 publications
2
132
0
Order By: Relevance
“…Therefore, it was used as standard of reference for the diagnosis. Indeed, a recent study demonstrated both laparotomy and laparoscopic exploration can effectively identify the unknown primary lesion in patients presenting only with liver or node NETs metastases in 86.7% of the cases [13]. Moreover, the authors found multifocal intestinal lesions in 52.4% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was used as standard of reference for the diagnosis. Indeed, a recent study demonstrated both laparotomy and laparoscopic exploration can effectively identify the unknown primary lesion in patients presenting only with liver or node NETs metastases in 86.7% of the cases [13]. Moreover, the authors found multifocal intestinal lesions in 52.4% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CT, somatostatin receptor scintigraphy , enteroclysis, capsule endoscopy, and magnetic resonance imaging enteroclysis have all been found to have some utility for identifying the primary tumor (Picus, Glazer et al 1984;Sugimoto, Lorelius et al 1995;Bader, Semelka et al 2001; van Tuyl, Kuipers et al 2004;Johanssen, Boivin et al 2006). Recently, the sensitivity of diagnostic methods for locating primary tumors in a larger number of patients with well differentiated NET liver metastases was reported by Wang et al (Wang, Parekh et al 2010 In the study by Wang et al, 15 patients with NET liver metastases and unknown primary tumor underwent surgical exploration, 7 of which were laparoscopic. The primary tumor was located in most (87%) patients (Wang, Parekh et al 2010).…”
Section: Methods For Identifying the Primary Sitementioning
confidence: 99%
“…Recently, the sensitivity of diagnostic methods for locating primary tumors in a larger number of patients with well differentiated NET liver metastases was reported by Wang et al (Wang, Parekh et al 2010 In the study by Wang et al, 15 patients with NET liver metastases and unknown primary tumor underwent surgical exploration, 7 of which were laparoscopic. The primary tumor was located in most (87%) patients (Wang, Parekh et al 2010). All identified tumors were in the small intestine.…”
Section: Methods For Identifying the Primary Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic diagnostics of the small intestine is usually undertaken to identify the primary tumour site in the case of metastases of an unknown origin (often significantly larger than the primary tumour), in the case of non-specific abdominal symptoms, or to find the cause of gastrointestinal bleeding [43].…”
Section: Endoscopic Diagnosticsmentioning
confidence: 99%